Variability of Sea Breezes Over the Cameroonian Coast and Their Interaction With the West African Monsoon - Kouogang Tchuenkam, Fabius Cédric; Mama, Anselme Crépin; Gah-Muti, Salvanus Yevalla; Araujo, Moacyr (Frontiers in Earth Science, 2022)
The sea breeze characteristics of over two coastal areas of Cameroon were studied. The study used 3-hourly wind (speed and direction), rainfall, and atmospheric pressure data of 4 years (2006–2009) at Tiko and 5 years (2011–2015) at Ebodje to examine various characteristics of sea breezes. Statistics are presented that describe the occurrence, onset and cessation, and strength of the sea breezes. The frequency of occurrence clearly shows two regimes by two maxima (November and March) at Tiko and (January and July) at Ebodje. The results show that a sea breeze usually starts few hours (about 3–4 h) after the sunrise as a light onshore surface wind, has a mean duration of about 9 h at Tiko, and occurs during all seasons at both coastal areas. The sea breeze occurrence is found to be strongly influenced by the West African monsoon winds, and its onset and cessation times show a pronounced seasonal variation. The sea breeze strength is greater at Tiko than that at Ebodje during the West African monsoon season. Average daily hodographs for Tiko reveals that the sea breeze circulation is in both clockwise and anticlockwise rotation. There would be a significant seasonal effect of large-scale flows on sea breeze hodograph patterns. A wind roses analysis at Ebodje shows a high temporal variability of sea breeze frequencies at 09:00 (Local Standard Time: LST) in the south direction (36%), then at 15:00 LST in the west direction (26%), because of the preponderance of calm atmospheric situations conducive to its onset. Therefore, the circulation of the sea breeze is influenced by local factors (topography and vegetation). This phenomenon in the coastal regions of Cameroon can be the main factor controlling the transport of accidental near shore oil slicks and air pollutants.